Evaluation of the Interactions between Hydrogen and Steel in Geothermal Conditions with H2S - Kittel, Jean; Ropital, François; Grosjean, François; Joshi, Gaurav (HAL CCSD, 2020)
International audience Geothermal fluids combine high temperature and high pressure conditions, leading to a severe risk of corrosion for the steel materials used in the well. Corrosivity is enhanced when acid gases such as CO 2 and H 2 S are present. In addition to localized or uniform corrosion, H 2 S also promotes hydrogen entry into the steels, resulting in a reduction of mechanical strength. Depending on the metallurgical properties of the steel and on the applied stresses, cracking may occur. Different types of H 2 S related cracking mechanisms have been identified, i.e. HIC (hydrogen induced cracking), or SSC (sulfide stress cracking), mainly based on the experience of oil and gas production where H 2 S is often present. It is well recognized that 2 parameters govern the risks of hydrogen related failures, i.e. the instantaneous hydrogen flux at the metal surface related to the electrochemical reduction of proton associated with the corrosion reaction, and the cumulated amount of hydrogen dissolved in the metal. In order to examine these parameters, an original experimental device was used, allowing measuring hydrogen permeation in steel exposed to high-temperature / high-pressure environment. In parallel to the permeation measurements, HIC cracking experiments were performed. A good correlation was found between the extent of internal cracking and the hydrogen flux, for various experimental conditions in a pH range between 3.5 and 5.5, and H 2 S partial pressure between 0.01 bar and 1 bar.